Ecology and Transmission Dynamics of Ostertagia gruehneri in Barrenground Caribou ... - Hoar, Bryanne (Graduate Studies, 2012)
Climate change in the Arctic is occurring at an accelerated rate and is predicted to alter the ecology of northern ecosystems, including parasite transmission. Barrenground caribou are a keystone species of the tundra and the majority of herds have recently undergone population declines. Ostertagia gruehneri, the most common gastrointestinal parasite of Rangifer tarandus, has been shown to impact the population dynamics of reindeer through decreased food intake, weight loss, and reduced pregnancy rates. Ostertagia gruehneri has a direct life cycle that includes free-living stages. The development and survival rates of this parasite are influenced by climatic factors and its transmission will be affected by climate change. The aim of this research was to investigate how climate change may impact transmission dynamics of O. gruehneri in barrenground caribou. This aim was achieved by developing a more detailed understanding of the life cycle of O. gruehneri and the current transmission patterns within this ...